The Thomas crown affair - McQueen, Steve 1930-1980.; Dunaway, Faye.; United Artists Ltd.; Mirisch-Simkoe-Solar Productions; MGM/UA Home Video (Firm).; MGM Home Entertainment Inc. (Santa Monica, Calif. MGM Home Entertainment, 1997)
Thomas Crown (Steve McQueen) is a lone wolf in chic clothing. He's a Boston tycoon who masterminds a daring bank job, even though he doesn't need the money. What he needs is the thrill of the heist, the adrenaline rush of not getting caught. Catching crooks is where insurance investor Vicky Anderson (Faye Dunaway) comes in. She always gets her man. But this time she may be too much in love to give him up. McQueen and Dunaway are lovers and adversaries in The Thomas Crown Affair, a glossy cat-and-mouse caper directed by Norman Jewison (In the Heat of the Night, Moonstruck). Jewison makes exciting use of split-screen images as the action leaps from the boardroom to the boudoir, the polo field to a glider cockpit.
Summary from the cover.
Title from container.
Originally released as a motion picture in 1968.
writer, Alan R. Trustman ; music, Michel Legrand.
Steve McQueen, Faye Dunaway.
VHS ; Dolby Surround stereo
Donated by Prof. Amor Olaguer-Aljibe.
Keywords: Bank robberies -- Crimes against; Businessmen; Art thefts -- Drama; Art thefts -- Investigation; Action and adventure films; Insurance Investigators -- Drama